Contingent Variables to the Valuation Product Methods: empirical study of industrial portuguese SMEs - Machado, Maria João Cardoso Vieira (Review of Business Management, 2011)
The contingency theory is based on the premise that there is an ideal accounting system that applies equally to all organizations; it all depends on several contingent factors. Studies have identified several variables contingency methods of management accounting, however, none of these studies addressed the Small and Medium Enterprises (SMEs), which justifies research to conclude whether these variables contingency, now established in theory, are the same if we look at small businesses. The objectives of this study are related to the identification of relationships between the method of valuation of products used by SMEs and three contingent variables: firm size, type of production; the keeping of the capital. We have found statistically significant relationships between firm size and methods of goods valuation. The collected data also suggests a relationship between how the company values their products as well as the fact that they produce for stock or under orders, however the small number of observations did not allow validate this evidence statistically. Regarding to the shareholding, the information collected shows that there is no relationship between the type of society and the method of goods valuation. Key words: Contingency theory. Holding capital. Dimension.